PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG MENGGUNAKAN MICROSOFT ACCESS - Razaluddin, Muhammad; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
Inventory information system is something that is often heard in a company. A company that is engaged in trading of such distributions must be familiar with the inventory system. The use of manual recording has a negative impact on the company. Looking at company earnings and how many remaining items available manually require a long time. This research aims to design an inventory information system to help employees manage goods and find available items more easily so as to reduce mistakes made by employees. The system designed in this study uses Microsoft Access. This research uses descriptive qualitative method, data collection techniques in research conduct interviews, observation, and literature study conducted directly with the owner of the company. This research produces an application that can help control the inventory of goods more effectively and informally so that it can control the goods entering and leaving the company